Highly selective lanthanide-doped ion sieves for lithium recovery from aqueous solutions. Issue 2 (March 2023) - Zheng, Lu; Chen, Jin; Sun, Jianke; Liu, Min; Gao, Yuyu; Guo, Zhifeng
The increased global demand for lithium is rapidly depleting the lithium ore reserves. Therefore, attention has turned to the recovery of lithium from aqueous solutions, such as lithium-containing brine. Compared with other methods of lithium recovery, adsorption is energy efficient and simple to implement, increasing demand for selective lithium adsorbents. In this study, a selective lithium-ion adsorbent, H4 Ti5– x La x O12, was synthesized via the sol–gel method, followed by heat treatment and acid washing. The effects of the temperature and degree of lanthanum doping ( x ) on the crystalline phase, morphology, lithium-ion adsorption capacity, and lithium-ion selectivity of the ion sieve were investigated, and the optimal synthetic conditions were determined. We found that doping with La 3+ cations ( x  = 0.01) increased the lithium-ion adsorption capacity (23.96 mg g −1 at 25 °C at pH = 12; 8.2% higher than before doping), rate, and selectivity. In addition, the ion sieve could be used over multiple adsorption–desorption cycles with only a minor reduction in the lithium-ion adsorption capacity (22.88 mg g −1 ). Overall, these results suggest that doping with La 3+ cations stabilized the H4 Ti5– x La x O12 crystal structure, alleviated particle agglomeration, expanded the lithium-ion channels, and decreased the resistance to lithium-ion migration, thus improving adsorption performance. The findings suggest that the proposed ion sieve has practical applications in the selective recovery of lithium from aqueous solutions containing a mixture of metal ions.